Compassion for Trauma: Role of Self Compassion in Posttraumatic Growth of Fatherless among Orphanage Adolescents - Fitria, Annisa Zaenab Nur (Jurnal Ilmu Perilaku, 2024)
Individuals who have self-compassion tend to have more positive thoughts regarding traumatic experiences, which in turn will relate to better emotional outcomes. The struggles of individuals with great challenges in the life crisis will result in a positive change experience called posttraumatic growth (PTG). The study aims to see the relationship between self-compassion and posttraumatic growth in adolescence who have been fatherless (because of death) and living in the orphanage. The study participants were 100 adolescences (57 males and 43 females) aged 12-15 years. The selfcompassion variable is measured by Self-Compassion Scale (Neff, 2003), whereas posttraumatic growth variables are measured by the Post Traumatic Growth Inventory (Tedeschi & Calhoun, 1996) through the adaptation process. The results showed that there was a positive relationship between self-compassion and posttraumatic growth in adolescence that stayed in the orphanage (R = 0.252, p <0.01). In this research, the self-compassion aspect that the most impact for posttraumatic growth is self kindness (r = 0,351, p < 0.001) and common humanity (r = 0,303, p < 0.001).